Decision Support System for Selecting House using Analythical Hierarchy Process - Reza Zubaedah; Stanly Hence Dolfi Loppies; Fransiskus Xaverius (Information Technology and Science (ITScience), 2023)
Houses are the primary needs of everyone other than clothing and food needs. When consumers choose a house criteria that are used such as facilities, payment methods, type of house, land area, number of rooms, bathrooms, kitchens, living rooms, models, prices, developers and housing names. Sometimes choosing a house is difficult because of the many criteria that you always want to meet in accordance with consumer standards. The existence of a system is expected to help consumers provide alternatives in accordance with the choice of criteria as input and output systems in the form of alternative sequences of results from the system. The use of the Analytical Hierarchy Process (AHP) method solves a complex situation that is not structured into several components in a hierarchical arrangement, by giving subjective values ??about the relative importance of each variable, and determining which variables have the highest priority to influence the results. Data collection methods used are literature studies, interviews and observations. The test method is a test for interface functionality and application questionnaire. The results obtained by this system are in the form of a decision support system that can provide an alternative selection of houses that can be used as a comparison with the choice of criteria according to consumer